Localization of active promoters for eucaryotic RNA polymerase II in the long terminal repeat of avian sarcoma virus DNA. - Mitsialis, S A (1983)
The nucleotide sequences in the long terminal repeat of avian sarcoma virus that are recognized in vitro by HeLa cell RNA polymerase II have been identified. For this purpose, various 5' and 3' deletions were introduced into a cloned long terminal repeat fragment. The effects of these deletions on transcription initiation in HeLa whole-cell extracts were then studied. Three specific transcripts have been identified. The major transcript is initiated at nucleotide +1 (relative to the cap site). Deletion of the upstream sequence between -299 and -55 has no effect on the level of transcription from this start site, whereas deletion of the sequence downstream of -14 drastically reduces the levels of transcription. In contrast, deletion of the sequence downstream from the TATA box has no effect on the initiation or efficiency of synthesis of the two minor RNA species, which are initiated at around nucleotides -260 and -105. The transcription of these RNA products, however, is abolished by an upstream deletion between -299 and -55. These results suggest that HeLa cell RNA polymerase II recognizes in vitro more than one promoter site present in the long terminal repeat of the avian sarcoma virus genome and defines the sequences required for initiation of the major transcript.